Quantised conductance in a contact between metallic oxide crystals - COEY, JOHN MICHAEL DAVID (American Physical Society, 1998)
The conductance of a point contact between two crystals of metallic (La0.75Sr0.25)MnO3 shows steps as the contact is broken. A histogram of the conductance values observed in 60 breaks exhibits a series of sharp peaks at integer multiples of G0 = 2e2/h. Quantum conductance in these ceramics is qualitatively different from that normally seen in metals and suggests that no neck formation occurs during fracture of a contact between these brittle materials.
PUBLISHED
Keywords: Physics